Who are macro-community members: an answer from the viewpoint of Confucianism. Issue 3 (17th July 2020) - Lo, Hung Kei Kenneth
Abstract : Purpose: This paper aims to present and discuss the findings from a qualitative study of victim-offender mediation meetings in two non-government organisations in Hong Kong between January 2015 and February 2016. It argues that mediators in Hong Kong have a unique interpretation of the criteria for someone to be considered a "macro-community member". Confucian relational ethics emphasises that everyone lives in a personal nexus and wrongdoings will disturb this nexus. In this specific context, therefore, mediators feel that reconciliation and reparation should be dealt with by the people in the offender's network while the involvement of unknown macro-community members is discouraged. Design/methodology/approach: The semi-structured interview was adopted for use in this study, and an interview schedule with 12 open-ended questions was prepared as a guideline for conducting the interviews. Findings: Mediators in Hong Kong have a unique interpretation of the criteria for someone to be considered a "macro-community member" Confucian relational ethics emphasises that everyone lives in a personal nexus and wrongdoings will disturb this nexus. Reconciliation and reparation should be dealt with by the people in the network, and the involvement of macro-community members will certainly disturb this network. Originality/value: This study was conducted by the author between January 2015 and February 2016 for the purpose of obtaining a doctorate. The paper has neither been published previously nor is it under review for publication in any other journal at this time.